2020
DOI: 10.1016/j.taap.2020.115155
|View full text |Cite
|
Sign up to set email alerts
|

Exposures to uranium and arsenic alter intraepithelial and innate immune cells in the small intestine of male and female mice

Abstract: Human exposures to environmental metals, including uranium (U) and arsenic (As) are a global public health concern. Chronic exposures to U and As are linked to many adverse health effects including, immune suppression and autoimmunity. The gastrointestinal (GI) tract is home to many

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…A recent study noted U accumulation in Jurkat cells; however, accumulation did not induce cytotoxic effects . Medina et al reported significant immunotoxicity in the GI tract following chronic exposure to drinking water containing soluble U . In vitro studies on soluble U exposure in macrophages showed a significant decrease in cell viability and an induction of inflammatory responses (TNF-α secretion and MAPK activation) .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study noted U accumulation in Jurkat cells; however, accumulation did not induce cytotoxic effects . Medina et al reported significant immunotoxicity in the GI tract following chronic exposure to drinking water containing soluble U . In vitro studies on soluble U exposure in macrophages showed a significant decrease in cell viability and an induction of inflammatory responses (TNF-α secretion and MAPK activation) .…”
Section: Results and Discussionmentioning
confidence: 99%
“…39 Medina et al reported significant immunotoxicity in the GI tract following chronic exposure to drinking water containing soluble U. 42 In vitro studies on soluble U exposure in macrophages showed a significant decrease in cell viability 43 and an induction of inflammatory responses (TNF-α secretion and MAPK activation). 44 Only a few studies have investigated the toxicity of U as particulates.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recent report showed arsenic treatment impairs distinct population of intestinal stromal cells and intraepithelial and innate immune cells (Kellett et al 2022) (Medina et al 2020). In conjunction, the histology of colon sections of pAs-mice showed infiltration of inflammatory cells and goblet cell hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…2 The established maximum U contamination level in drinking water is 30 ppb. 3 Exposure to higher contamination levels can cause cardiovascular and neurological disorders, cancers, immunosuppression, and autoimmunity. [3][4][5][6] During exposure to depleted uranium, uranyl cation (UO 2 2+ ) binds to DNA in mammalian cells, forming a uranium-DNA (U-DNA) adduct that could cause mutations, thereby triggering a range of protein synthesis errors, some of which may lead to various cancers.…”
Section: Introductionmentioning
confidence: 99%
“…3 Exposure to higher contamination levels can cause cardiovascular and neurological disorders, cancers, immunosuppression, and autoimmunity. [3][4][5][6] During exposure to depleted uranium, uranyl cation (UO 2 2+ ) binds to DNA in mammalian cells, forming a uranium-DNA (U-DNA) adduct that could cause mutations, thereby triggering a range of protein synthesis errors, some of which may lead to various cancers. [7][8][9][10] A study on rat epithelial cells showed that uranium might induce signicant oxidative stress and a concomitant decrease in the anti-oxidative potential of lung tissues.…”
Section: Introductionmentioning
confidence: 99%